Ultrafine Nanoparticles of Poly(Methyl Methacrylate-co-Methacrylic Acid) Loaded with Aspirin. (14th August 2019) - López-Muñoz, R.; Treviño, M. E.; Morales, G.; Valdez-Garza, J. A.; Díaz de León, R.; Saade, H.; Enríquez-Medrano, F. J.; López, R. G.
Abstract : Nanoparticles of the poly(methyl methacrylate- co -methacrylic acid) or copolymer of P(MMA- co -MAA), were prepared by semicontinuous heterophase polymerization; they show a mean diameter of 12 nm and a 1.75 MMA/MAA molar ratio determined by carbon-13 nuclear magnetic resonance. The content of MAA, greater than that of Eudragit S100, copolymer of P(MMA- co -MAA) accepted by the FDA for the preparation of tablets, ensures its biocompatibility and its metabolism without toxic effects. Loaded with up to 22 wt. % aspirin, that is, acetylsalicylic acid (ASA), these nanoparticles increase slightly their size, according to transmission electron microscopy; however, the presence of ASA on the nanoparticle surface decreases their stability, which leads to a certain aggregation of the particles in the dispersion. Fourier transform infrared spectrometry was used for demonstrating the loading of ASA in the nanoparticles.